Adsorption of methyl orange and methylene blue dyes by lead sulphide modified calix[n]arenes (n=4,6,8) - Rosly, Nor Zida (2022)
Various industries around the world such as textile, printing, and leather industries have contributed to major sources of coloured wastewater that can cause severe water pollution. As a result, the current study aims to determine the adsorption behaviour of methyl orange (MO) and methylene blue (MB) dyes based on calix[n]arene-modified lead sulphide (PbS) (n=4, 6, 8) nanoadsorbents under optimal conditions. The calix[n]arene-modified PbS was formed by mixing 3-glycidoxypropyltrimethoxy silane, p-tert-butylcalix[n]arene, and PbS in dry toluene with triethylamine as a catalyst. Characterization studies using fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), and energy dispersive X-ray spectroscopy (EDX) revealed a successful synthesis of calix[n]arene-modified PbS. FTIR and EDX showed the presence of O–H stretching vibration, stretching vibration of C-CH3, C=C aromatic vibration, C-O stretching, carbon (C) and silicon (Si) which are evidence of successful immobilization of p-tert-butyl-calix[n]arene on the PbS surface. Morphological change from nanoparticles to flake-like structures is another indication the presence of p-tert-butyl calix[n]arene. According to the findings, the pH of point of zero charge (pHPZC) of the calix[4]arene-modified PbS, calix[6]arene-modified PbS, and calix[8]arene-modified PbS were pH 6.80, pH 7.28, and pH 7.31, respectively. Response surface methodology (RSM) was executed to develop a response surface for the optimization of adsorption conditions. The evaluation was further conducted to investigate the interactive effect of various factors (initial concentration, adsorbent dosage, contact time, pH, and temperature) on the adsorption of dye using a central composite design (CCD). The percentage removal of dyes from the water system was used to assess adsorption performance. The results of batch adsorption tests are presented in the study, which include the adsorption capacities, kinetics, and isotherms of the MO and MB adsorption processes. The isotherm parameters were determined using the Langmuir and Freundlich equilibrium models. The isotherm study of MO adsorption by calix[4]arene-modified PbS were best fitted by the Freundlich, indicating adsorption on heterogenous surfaces. In contrast, the isotherm studies of MB adsorption by calix[4]arene-modified PbS, calix[6]arene-modified PbS, and calix[8]arene-modified PbS were best described by the Langmuir, suggesting monolayer adsorption onto homogenously distributed adsorption sites of the adsorbent surfaces. The fitted model with the maximum adsorption capacity (qmax) of 3.268 mg/g, was discovered for the adsorption of MO by calix[4]arene-modified PbS. Meanwhile, the qmax for MB adsorption by calix[4]arene-modified PbS, calix[6]arene-modified PbS, and calix[8]arene-modified PbS were found to be 5.850 mg/g, 5.495 mg/g, and 11.90 mg/g, respectively. Pseudo-first order and pseudo-second order of kinetic studies were demonstrated for their quality to fit the data. The adsorption kinetics of MO adsorption by calix[4]arene-modified PbS, MB adsorption by calix[4]arene-modified PbS, calix[6]arene-modified PbS, and calix[8]arene-modified PbS were well described by the pseudo-second order model suggesting that the adsorption on the adsorbent’s surfaces occurred via chemical adsorption. The reusability and leaching tests were performed to reduce the adsorbent disposal issues. The results showed that the adsorbents synthesized were stable, and there was a low risk of contaminant (Pb) released into bodies of water. Adsorption mechanisms such as electrostatic interaction, hydrogen bonding interaction, Yoshida hydrogen bonding interaction, and π-π interactions were proposed for dye adsorption on calix[n]arenes-modified PbS. Overall, the research presented novel adsorbents, calix[n]arenes-modified PbS, and a reusability strategy that could be used as alternative adsorbents in MO and MB dye removal and environmentally sustainable dye wastewater treatment.